2008
DOI: 10.1093/ee/37.2.333
|View full text |Cite
|
Sign up to set email alerts
|

Does Dietary P Affect Feeding and Performance in the Mixed-Feeding Grasshopper (Acrididae)Melanoplus bivitattus?

Abstract: Although consequences of limited dietary protein and carbohydrate to performance are well studied for terrestrial insect herbivores, the importance of phosphorus (P) remains poorly understood. We examined the significance of dietary P to performance in fifth-instar nymphs of the grasshopper Melanoplus bivittatus fed artificial diets. Consumption, digestion, developmental rate, and growth in response to different levels of P nested within standard-Protein and carbohydrate diets were determined. Developmental ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
16
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(19 citation statements)
references
References 45 publications
2
16
1
Order By: Relevance
“…However, diets with a P content of 0.1% and below or 1% and above could support maximal growth during 3 day time periods when animals had been fed on the optimal (0.5%) diets for most of their lives, suggesting insects have a considerable capacity to buffer effects of non-optimal P consumption. Long-term consumption of diets with a P content of 1.00% or higher suppressed growth, consistent with the 'intake target' behavior of S. americana and with observations of reduced performance of various aquatic consumers (Boersma and Elser, 2006) and some insect species when provided with diets well above the mean P levels for terrestrial leaves (Harrison et al, 2014;Loaiza et al, 2008;Smith, 1960). Together, these results demonstrate that ecologically relevant variation in plant P content affects the behavior and performance of this grasshopper.…”
Section: Discussionsupporting
confidence: 79%
See 3 more Smart Citations
“…However, diets with a P content of 0.1% and below or 1% and above could support maximal growth during 3 day time periods when animals had been fed on the optimal (0.5%) diets for most of their lives, suggesting insects have a considerable capacity to buffer effects of non-optimal P consumption. Long-term consumption of diets with a P content of 1.00% or higher suppressed growth, consistent with the 'intake target' behavior of S. americana and with observations of reduced performance of various aquatic consumers (Boersma and Elser, 2006) and some insect species when provided with diets well above the mean P levels for terrestrial leaves (Harrison et al, 2014;Loaiza et al, 2008;Smith, 1960). Together, these results demonstrate that ecologically relevant variation in plant P content affects the behavior and performance of this grasshopper.…”
Section: Discussionsupporting
confidence: 79%
“…grew faster on diets enriched in P (Frost and Elser, 2002). However, the development rate of the grasshopper Melanoplus bivittatus was unaffected by dietary %P of artificial diets, except for negative effects at the highest levels (Loaiza et al, 2008). Smith (1960) found similar results for M. bivittatus using fertilized wheat, as did Harrison et al (2014), who found no effects of dietary P intake on most fitness parameters of crickets (Gryllus veletis) except for some negative effects of high dietary P on male chirping rate.…”
Section: Introductionmentioning
confidence: 73%
See 2 more Smart Citations
“…Melanoplus bivittatus , described as a forb specialist by Joern (1979) and a generalist by Isely (1944) and Loaiza et al. (2008), also had high niche breadth values and multiple plant families present in the gut, making it a generalist. Chortophaga viridifasciata , described as a generalist by Joern (1979) and Tuberville et al.…”
Section: Discussionmentioning
confidence: 99%